Comparative Studies On Digestive Efficiency And Urea Kinetic Between Goat And Sheep - Darlis, (1995)

(untitled)
A study was conducted to compare the digestive efficiency and urea kinetics between Malaysian indigenous goats and sheep fed rice straw + soybean meal (SSB) and rice straw + soybean meal + sago (SSG). The Dry Matter (DM), Nitrogen (N), Organic Matter (OM) and Energy (E) intakes in goats and sheep were similar when fed SSB diet, but with SSG diet, DM intake of goats was higher than sheep, while no significant differences in N, OM and E intakes were observed.With SSB diet, goats could digest ADF significantly (P<O.05) more than sheep, but sheep showed higher (P<O.05) digestibility values for Crude Protein (CP), OM and E than those of goats. However, with SSG diet only digestibility values for E were significantly different between the two animal species. Potential degradability for DM and NDF of straw were higher (P<O.05) in goats than sheep when fed SSB diet. However, goats had lower values (P>O.05) in N potential degradability of Soybean Meal (SBM) than sheep. Studies in rumen fluid parameters showed that ammonia concentration was higher in sheep (3 82.89 ± 3 3 .76 mg Nil) than goats (363.24 ± 43.42 mg N/l), while pH and total Volatile Fatty Acid (VFA) concentrations were similar between the two species when fed SSB diet. The molar proportion of acetate in goats was higher (79. 13 ± 2 .95%) than that in sheep (75.84 ± 3 .91 %), but the reverse was true for molar proportion of propionate where the values obtained for sheep and goats were 15 .57 ± 2 .40% and 17.96 ± 2.72%, respectively. No significant difference in molar proportion of butyrate was observed between the two animal species.